Preface - Zimnoch-Guzowska, Ewa (Plant Breeding and Seed Science, 2004)
Potato Late Blight is one of the most devastating diseases worldwide. The yearly losses reach up to 10-15 % of the global crop, which is comparable to the total potato production in the EU countries. There are several national and international programs and initiatives to stimulate progress in breeding potato cultivars resistant to Late Blight. Here, the Global Initiative on Late Blight (GILB), joined by researchers from all continents, several finished and ongoing EU programs directed to the progress in Late Blight research as well as the Cornell-Eastern Europe-Mexico (CEEM)International Collaborative Project in Potato Late Blight Control need to be mentioned...